Truth as Identity; [Verdad Como identidad1 - Briceno-Dominguez, J (Universidad De Valparaíso, Chile, 2023)
My aim in this article is to defend the essential core of the theories of truth that understand truth as identity, namely: that the truth-bearer is the truth-maker. In particular, I am interested in defending the version of Hornsby (1997) and McDowell (1994) against the attacks made by Dodd (1995; 1999; 2008). My defense is applicable to previous versions belonging to this family of theories, especially to that of Moore (1899; 1902). © 2023 University of Valparaiso. All rights reserved.